Relevance of career services for CEMS students for successful job-entry - Zicháčková, Denisa; Machková, Hana; Králová, Tereza, 1978-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
The thesis aims at exploring what the role of career guidance services for CEMS students in their job search is, and at proposing a number of recommendations for further development of CEMS career services. First part of this thesis will provide us with a necessary theoretical background on career choice, career management and development, and career guidance. Then, CEMS and its current career services offer will be presented in brief. Finally, an analysis of a research that we have conducted within CEMS graduates community will enable us to formulate a number of recommendations for CEMS career services improvement.
Vedoucí práce: Hana Machková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses